Enhancement of the Stability of a Prolipase from Rhizopus oryzae toward Aldehydes by Saturation Mutagenesis - Di Lorenzo, Mirella (American Society for Microbiology (ASM), 2007)
A prolipase from Rhizopus oryzae (proROL) was engineered in order to increase its stability toward lipid oxidation products such as aldehydes with the aim of improving its performance in oleochemical industries. Out of 22 amino acid residues (15 Lys and 7 His) prone to react with aldehydes, 6 Lys and all His residues (except for the catalytic histidine) were chosen and subjected to saturation mutagenesis. In order to quickly and reliably identify stability mutants within the resulting libraries, active variants were prescreened by an activity staining method on agar plates. Active mutants were expressed in Escherichia coli Origami in a 96-well microtiterplate format, and a stability test using octanal as a model deactivating agent was performed. The most stable histidine mutant (H201S) conferred a stability increase of 60%, which was further enhanced to 100% by combination with a lysine mutant (H201S/K168I). This increase in stability was also confirmed for other aldehydes. Interestingly, the mutations did not affect specific activity, as this was still similar to the wild-type enzyme.